Changes of Corneal Wavefront Aberrations in Dry Eye Patients after Treatment with Artificial Lubricant Drops - Ning Lu; Fangyu Lin; Zhu Huang; Qin He; Wei Han (Journal of Ophthalmology)
Purpose. To evaluate the corneal aberration changes in dry eye patients after treatment with artificial eye drops. Methods. Thirty mild to moderate dry eye patients treated with artificial eye drops and twenty comparable dry eye patients were recruited as controls. Anterior corneal aberrations over 3 mm and 5 mm analytical zones including total, 3rd to 5th high order aberrations (HOAs), spherical aberration (SA), and vertical (V-coma) and horizontal coma (H-coma) obtained from corneal topography data at baseline and 2 weeks after treatment were evaluated. Results. For 3 mm zone, trefoils, V-coma, H-coma terms, and 3rd and 5th HOAs were significantly decreased (p<0.05) in the treatment group. For 5 mm zone, instillation of eye drops reduced H-coma, SA terms, 3rd to 5th orders, and total HOAs all showed a significant decrease (p<0.05). The root mean square analysis of the Zernike terms also showed similar statistical results. For control group, all individual terms and total HOAs did not have significant changes over 3 mm and 5 mm zones (p>0.05). Conclusions. Treatment with artificial eye drops can effectively improve the corneal optical quality of dry eye patients by ameliorating the HOAs of anterior corneal surface.